Contemporary Islamic Ethics: An Analysis of Tariq Ramadan’s Perspectives on the Jurisprudence of Minorities and the Realities of Life in the West - Nurlela, Andi; Aprianif; Rofiq, Muhammad Ainur; Abdullah, Yazeed Ghinan; Nizar, Akhmad; Rohmawati, Hanung Sito (Journal of Islamic Thought and Civilization, 2025)
Every society is built upon particular values, and for Muslims, Islam provides the core framework that unites and guides their lives. In Western secular societies, however, Muslims face a dual challenge: integrating/assimilating successfully into the broader community while also preserving their Islamic identity and overcoming social barriers. To address this, Tariq Ramadan advocates for a dynamic hermeneutics of maqāṣid al-sharīʿah, positioning it as an ethical framework within Islamic methodology. Yet, his approach has not gone without critique. Scholars, such as al-ʿAlwānī, have advanced the concept of fiqh al-aqalliyyāt (minority jurisprudence) as an alternative way of responding to the unique realities of Muslim life in the West. This study explored contemporary Islamic ethics through the lens of Tariq Ramadan’s thought, with a particular focus on minority jurisprudence and the lived experiences of Muslim minorities in the West. Drawing on qualitative, library-based research, the study examined Ramadan’s key writings to assess his contributions. The findings indicated that Ramadan’s vision goes beyond offering an alternative to fiqh al-aqalliyyāt. It presents a more integrative framework that enables Muslims in the West to navigate their faith in harmony with modern life. In this process of identity formation, Ramadan works towards reconciling Islam with citizenship and the values of Western civilization. From an economic standpoint, Ramadan does not reject capitalism outright but calls for moral reforms that align economic activity with Islamic principles and social justice values, such as equity, sustainability, and community welfare. In this way, he reframes the presence of Muslims in the West not as a theological anomaly or an exception to Islamic tradition, however, as a legitimate and enriching force that contributes to the broader ethical fabric of society. This study, therefore, added to the wider discourse on contemporary Islamic ethics. Moreover, it highlighted the role of minority jurisprudence in shaping the lived experiences of Muslim communities in Western contexts.